172 An unusual case of congenital myasthenic syndrome: the mechanism for treatment response. Issue 3 (9th February 2012) - Spillane, J; Kullmann, D M; Beeson, D; Howard, R S
Abstract : Congenital myasthenic syndromes (CMS) are a heterogenous group of inherited disorders that impair neuromuscular transmission. Mutations in the gene that codes for the epsilon subunuit (CHRNE) of the Acetylcholine receptor (AChR) are well recognised causes of CMS and can cause primary AChR deficiency or altered channel kinetics. We describe an unusual case of CMS in a patient who is a compound heterozygote for two mutations in the CHRNE gene. The patent is a 66-year-old man with a negative family history who presented in childhood with limb weakness and ptosis. He has nocturnal hypoventilation and has required two ICU admissions for respiratory failure. Electrophysiological studies revealed a decremental response to repetitive nerve stimulation and increased jitter with blocking on EMG. Genetic analysis revealed two different CHRNE mutations: a maternally inherited deletion (p.278del) and a paternally inherited point mutation (p.R217L). The deletion has been shown to cause a slow channel syndrome whereas the point mutation causes a decrease in AChR channel expression. The patient's condition has improved with combination treatment with fluoxetine, salbutamol and neostigmine. This unusual case demonstrates the phenotypic variability of CHRNE mutations provides a mechanistic explanation for the treatment response.